Preliminary screening of endophytic fungi from Enicostemma axillare (Lam.) Raynal. for antimicrobial activity - Deepake, Ujwala S; Das, Yamilee; Algunde, Shital; Gyananath, G (Current Botany, 2013)
Enicostemma axillare (Lam.) Raynal. belonging to Gentianaceae family is a perennial herb found throughout India and is reported to possess medicinal properties. Considering the importance of this plant, a study was conducted to determine the colonization frequency of endophytic microbes and to evaluate the antimicrobial activity of crude extracts of fungal endophytes from Enicostemma axillare. The endophytic fungi from different parts of the plant (leaves, stem and roots) were isolated, pure cultures were raised and identified based on the morphology and characteristics of fungal spores. The highest colonization frequency of bacteria and actinomycetes was observed in leaves (100 %). However, colonization frequency of endophytic fungi was around 92 % higher in stem. The endophytic fungi that displayed broad spectrum antimicrobial activity include Aspergillus flavus, Penicillium sp., Eurotium sp., Sartorya sp. and Phomopsis sp. Our preliminary results indicate that crude extracts of endophytic fungi of Enicostemma axillare (Lam.) Raynal. may possess some antimicrobial compounds.